An Implementation Analysis of AHP-TOPSIS and Music-3D for Optimizing Spare Part Inventory Control (Case Study: PT. Bati) - Kelvin Leo; Siti Rahayu; Tri Ngudi Wiyatno (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study proposes an integrated spare part inventory control decision-making model using AHP-TOPSIS and MUSIC-3D. While previous studies applied these methods independently, this research combines them within a general trading context to address procurement prioritization and inventory segmentation. AHP was used to assign weights to three inventory criteria: annual consumption (ABC), turnover rate (FSN), and unit price (HML). These weights informed the TOPSIS ranking of 50 spare parts, identifying high-priority items such as MRCT 430 and WLOR XR96. MUSIC-3D further classified items into 16 multidimensional categories to support differentiated control strategies. A one-month implementation at PT. BATI demonstrated improvements in stock control and cost efficiency. The model provides a structured, scalable framework for companies facing high inventory complexity. Keywords: Inventory Management, AHP, TOPSIS, MUSIC-3D, Spare parts, Multi-Criteria Decision Making